Relationship between Santri's Personal Hygiene to the Incidences of Scabies in Islamic Boarding School - Maria Ulfa; Dwi Puspitarini, Marinda; Gumilang, Retna; Ideham, Bariah; Agnovianto, Yuriske (Universitas Nahdlatul Ulama Surabaya, 2025)
Background: Skin diseases are often found in Indonesia, such as scabies which is caused by parasites. Scabies causes damage to the skin and discomfort due to itching. This scabies disease is not paid enough attention by students in Islamic boarding schools, the causes are poor environment, poor personal hygiene, lack of knowledge so that there is a risk of transmission of scabies disease. Therefore, this is a priority that needs to be considered and addressed in order to reduce the risk of transmitting scabies in the Islamic boarding school environment. Research objective: to analyze the relationship between the level of personal hygiene knowledge and the incidence of scabies in Islamic boarding school. Method: This type of research is analytical observational survey study with a cross sectional approach. Data collection uses questionnaires. Sampling is total sampling. Data processing and analysis uses chi square analysis. Results: The results of the Chi Square analysis show that the value of p=0.009 (p<0.05), which means that there is a significant relationship between the level of personal hygiene knowledge and the incidence of scabies in students at Islamic boarding schools. Conclusion: The level of knowledge of students about personal hygiene is one of the factors that can influence the transmission of scabies in the Islamic boarding school environment. So the level of knowledge of students must be increased so that it can be a way to prevent the transmission of scabies.